(untitled) (Baghdad Science Journal, 2021)
A new generalizations of coretractable modules are introduced where a module is called t-essentially (weakly t-essentially) coretractable if for all proper submodule of , there exists f End( ), f( )=0 and Imf tes (Im f + tes ). Some basic properties are studied and many relationships between these classes and other related one are presented.